Online self-regulated learning strategies amid a global pandemic: Insights from Indonesian university students - Mahmud, Yogi Saputra; German, Emilius (Universiti Utara Malaysia Press, 2021)
Purpose – At the beginning of 2020, the COVID-19 pandemic affected many aspects of life, including education. In response, the Indonesian government mandated all educational institutions, including universities, to implement online learning. Through online learning, many university students experienced considerable changes in the way they regulated their knowledge-seeking process. This research examined the level of EFL university students' self-regulated learning during their online learning activities for an English academic writing course, as well as the difficulties encountered and strategies developed in the online learning context.